2018
DOI: 10.1186/s13007-018-0382-8
|View full text |Cite
|
Sign up to set email alerts
|

A simple and efficient CRISPR/Cas9 platform for induction of single and multiple, heritable mutations in barley (Hordeum vulgare L.)

Abstract: BackgroundGenome editing of monocot plants can be accomplished by using the components of the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeat/CRISPR associated Cas9) technology specifically optimized for these types of plants. Here, we present the development of RNA-guided Cas9 system for simplex and multiplex genome editing in barley.ResultsWe developed a set of customizable RNA-guided Cas9 binary vectors and sgRNA modules for simplex and multiplex editing in barley. To facilitate the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 71 publications
1
61
1
3
Order By: Relevance
“…Transcriptional and translational enhancer sequences have been reported to improve Cas9 expression and, in turn, the efficiency of CRISPR/Cas9‐mediated targeted mutagenesis in plants (Gasparis et al ., ; Kusano et al ., ). We therefore investigated whether the omega translational enhancer from tobacco mosaic virus (TMV) would improve gene targeting by enhancing Cas9 translation (Gallie and Kado, ; Mitsuhara et al ., ; Figure a).…”
mentioning
confidence: 97%
“…Transcriptional and translational enhancer sequences have been reported to improve Cas9 expression and, in turn, the efficiency of CRISPR/Cas9‐mediated targeted mutagenesis in plants (Gasparis et al ., ; Kusano et al ., ). We therefore investigated whether the omega translational enhancer from tobacco mosaic virus (TMV) would improve gene targeting by enhancing Cas9 translation (Gallie and Kado, ; Mitsuhara et al ., ; Figure a).…”
mentioning
confidence: 97%
“…The efficiency of CRISPR/Cas9-induced mutations in the primary transformants ranged from 5-35% in this study. Previous studies in barley reported CRISPR/Cas9-induced mutation frequencies of 10-23% (Lawrenson et al, 2015), 44% (Holme et al, 2017) and ~80% (Gasparis et al, 2018;Kapusi et al, 2017) of plants after Agrobacterium-mediated transformation. In other cereals such as wheat, mutant production efficiency was reported from 0.3-5% using biolistic bombardment of CRISPR/Cas9 components (Zhang et al, 2016;Gil-Humanes et al, 2017;Liang et al, 2017;Sánchez-León et al, 2018) and Agrobacterium-mediated transformation (Okada et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The CRISPR/Cas9 system has been successfully used for genome editing in a variety of monocots, including rice (Oryza sativa), wheat (Triticum sp. ), barley (Hordeum vulgare), and maize (Zea mays) (Feng et al 2018;Gasparis et al 2018;Hu et al 2018;Kis et al 2019;Okamoto et al 2017;Wang et al 2017;Zhang et al 2016). To perform CRISPR/Cas9-mediated genome editing, the Cas9 endonuclease is guided by a single guide RNA (sgRNA) to recognize the complementary sequence and create double-strand breaks (DSBs), thereby generating a short deletion or insertion.…”
mentioning
confidence: 99%